Pathogenic variation in Colletotrichum gloeosporioides infecting Stylosanthes spp. in a center of diversity in Brazil - Chakraborty, S.; Fernandes, C. D. [UNESP]; Charchar, M. J. D.; Thomas, M. R. (Amer Phytopathological Soc, 2002)
Pathogenic variation in Colletotrichum gloeosporioides infecting species of the tropical pasture legume Stylosanthes at its center of diversity was determined from 296 isolates collected from wild host population and selected germ plasm of S. capitata, S. guianensis, S. scabra, and S. macrocephala in Brazil. A putative host differential set comprising 11 accessions was selected from a bioassay of 18 isolates on 19 host accessions using principal component analysis. A similar analysis of anthracnose severity data for a subset of 195 isolates on the 11 differentials indicated that an adequate summary of pathogenic variation could be obtained using only five of these differentials. of the five differentials, S. seabrana 'Primar' was resistant and S. scabra 'Fitzroy' was susceptible to most isolates. A cluster analysis was used to determine eight natural race clusters using the 195 isolates. Linear discriminant functions were developed for eight race clusters using the 195 isolates as the training data set, and these were applied to classify a test data set of the remaining 101 isolates. All except 11 isolates of the test data set were classified into one of the eight race clusters. Over 10% of the 296 isolates were weakly pathogenic to all five differentials and another 40% were virulent on just one differential. The unclassified isolates represent six new races with unique virulence combinations, of which one isolate is virulent on all five differentials. The majority of isolates came from six field sites, and Shannon's index of diversity indicated considerable variation between sites. Pathogenic diversity was extensive at three sites where selected germ plasm were under evaluation, and complex race clusters and unclassified isolates representing new races were more prevalent at these sites compared with sites containing wild Stylosanthes populations.
Keywords: geographical distribution; pathogen diversity; race composition; virulence analysis